A review on preparation techniques for synthesis of nanocrystalline soft magnetic ferrites and investigation on the effects of microstructure features on magnetic properties - Hajalilou, A. (Springer Verlag, 2016)
Soft magnetic materials have been used in many applications, i.e., electrical and electronic industries, due to their desirable electromagnetic characteristics. The performance of these materials in bulk form, where the size of grains is in micrometer scale, is only limited to a few megahertz frequencies due to their higher conductivity and domain wall resonance. Synthesizing the ferrite particles in nanometer scales before compacting them for sintering would be one way to solve using these materials at higher frequencies. The properties of ferrite depend mainly on the technique and conditions of preparation, which, in turn, affect the cation distribution over the tetrahedral and octahedral sites. Thus, the aim of this study was to introduce some methods used for synthesizing nanocrystalline soft magnetic ferrites. Furthermore, the microstructure features, i.e., grain sizes and porosities, which are influenced by the types of method used for preparation, playing key role on the magnetic properties of the sample, are also highlighted.